Motivasi Pasien Dalam Prilaku Pengendalian Diet Hipertensi Di Puskesmas Cibiru Kota Bandung - Dede Nur Aziz Muslim; Sri Mulyati Rahayu (NHM PRESS, 2021)
The number of incidence of hypertension is estimated to be able to cause 7.5 million deaths and about 12.8% of all deaths. WHO data in 2013 shows the prevalence of hypertension sufferers at the age of 25 years and over reaches 40%. Hypertension can be prevented and overcome by maintaining a lifestyle such as adherence to a diet low in fat, low in cholesterol, low in salt and reducing foods high in potassium and caffeine, regular exercise, not consuming alcohol, avoiding stress and controlling blood pressure regularly. Intrinsic motivation is motivation that arises in the patient, such as interests, attitudes and needs. If intrinsic motivation is good, it will encourage patients to adopt a diet according to the recommendations of health workers. Descriptive research design. The research was conducted at the Cibiru Health Center, Bandung City. The population is residents who have hypertension in Cibiru Village, the study sample is 30 hypertension patients. Collecting data using a questionnaire with the validity test value r table = 0.632 (n = 10). So that all questions are said to be valid, while the results of the reliability test value 0.984 means reliable. The results showed that motivation from attitudes and interests were mostly favorable, while most of the needs were unfavorable. Suggestions need to do further research on extrinsic motivation in controlling hypertensive patients